Turning 18: What a difference application of adult criminal law makes - Horst Entorf (Institute for the Study of Labor (IZA), 2011)
This paper contributes to the literature on specific deterrence by addressing the issue of selecting adolescents into adult and juvenile law systems. In Germany, different from the U.S. and most other countries, turning a critical cutoff age does not cause a sharp discontinuity from juvenile to adult penal law, but rather implies a shift to a discretionary system of both adult and juvenile law, dependent on the courts' impression of moral and mental personal development of the adolescent at the time of the act. The German legal system draws the line of adulthood at some fuzzy age interval between 18 and 21, which is well above the thresholds prevailing in the U.S. (16 to 18 years, state specific) and other countries such that the German evidence entails some external evidence to the previous literature mostly relying on U.S. data. Based on a unique inmate survey and two-equation models controlling for selectivity problems, results show that application of adult criminal law instead of juvenile penal law decreases expected recidivism of adolescents.
urn:nbn:de:101:1-201104113077
Keywords: K14; C52; K42; H11; 330; crime; recidivism; treatment effects; selection; survey data; Jugendkriminalität; Strafe; Wirkungsanalyse; Schätzung; Deutschland